2017
DOI: 10.18869/nrip.hdq.2.2.79
|View full text |Cite
|
Sign up to set email alerts
|

The Youth and Experience of Traffic Accidents (Grounded Theory)

Abstract: Background: Traffic accidents are among major causes of death all over the world. In Iran, it has become a social problem, with lots of people involved in; and the youth include the most victims of traffic accidents. The main objective of this research is to review the experience of the youth (18-24 years old in Tehran, Iran) with traffic accidents, and to develop a model to specify the factors. Materials and Methods: This study is based on Grounded Theory, in which a sample group of 50 young people, 18-24 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…According to the WHO Global Burden of Disease Project, road traffic accidents caused 1.27 million deaths in 2004. The road traffic injuries exert a considerable economic burden worldwide, especially in developing countries, which are under pressure to provide their developmental needs [3,4]. The global financial loss due to road traffic injuries are estimated to be US $518 billion and it costs governments between 1% and 3% of their gross national product.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the WHO Global Burden of Disease Project, road traffic accidents caused 1.27 million deaths in 2004. The road traffic injuries exert a considerable economic burden worldwide, especially in developing countries, which are under pressure to provide their developmental needs [3,4]. The global financial loss due to road traffic injuries are estimated to be US $518 billion and it costs governments between 1% and 3% of their gross national product.…”
Section: Introductionmentioning
confidence: 99%
“…According to the Legal Medicine Organization of Iran, 23362 trafficrelated deaths were recorded in the 2009-2010 period and 22974 in the 2008-2009 period [5]. Traffic accidents in Iran have become a social problem and are among the significant causes of death [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, culture building should be considered from the early age in schools and subsequently in universities in a continuous and integrated manner to teach cautiousness, discipline, and obeyance of laws and rules [29]. Results of the present study are fully explicable in the form of a planned behavior model.…”
Section: Discussionmentioning
confidence: 67%
“…Finally, this is very important to begin the trainings about caution, following the rules and discipline from the younger ages and during school times. This can be complemented in universities in continuous and unified approaches [20]. The results of research about driving aspects indicated that agreeable and aggressive personality traits with B coefficient of 0.37, 0.25 could predict violations among girls.…”
Section: Discussionmentioning
confidence: 99%